plz plz plz answr it fast
Attachments:
![](https://hi-static.z-dn.net/files/da6/545a15817ee87667f40023e3cc26dbd6.jpg)
Answers
Answered by
1
7(a³+8b³)
=> 7[(a)³+(2b)³]
using a³+b³ = (a+b)(a²+b²-ab)
7(a+2b)(a²+4b²-2ab)
hope this helps
=> 7[(a)³+(2b)³]
using a³+b³ = (a+b)(a²+b²-ab)
7(a+2b)(a²+4b²-2ab)
hope this helps
anusha191:
plz
Answered by
2
hey
here's ur answer!!
7a³ + 56b³
= 7(a³+8b³)
= 7[a³+ (2b)³]
=7(a+2b)(a² -2ab + b²)
hope it helps!!
here's ur answer!!
7a³ + 56b³
= 7(a³+8b³)
= 7[a³+ (2b)³]
=7(a+2b)(a² -2ab + b²)
hope it helps!!
Similar questions